1988
DOI: 10.1172/jci113585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and gestational regulation of corticotropin-releasing hormone messenger RNA in human placenta.

Abstract: Corticotropin-releasing hormone (CRH), a hypothalamic neuropeptide involved in the regulation of ACTH secretion, has been detected by RIA in extracts of human placenta. We wished to determine whether this immunoreactive substance is a product of CRH gene expression in the placenta. We have found authentic human CRH (hCRH) mRNA in human placental tissue that is similar in size to hypothalamic CRH mRNA. Furthermore, the transcriptional initiation site for placental hCRH mRNA is identical to that previously predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
11

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(105 citation statements)
references
References 37 publications
5
89
0
11
Order By: Relevance
“…In order to explain the discordance between the high level of hypercortisolism and the mild degree of ACTH overexpression in the tumor cells, we raised the possibility that this NSET may express another hormone triggering the pituitary-adrenal axis. We therefore measured the expression of CRH mRNA in tumor extracts and found high levels in the liver NSET compared with fetal placental control tissue (17), while normal human liver did not express CRH. This finding suggested that ectopic CRH originating from the NSET may have triggered the pituitary production of ACTH, thus stimulating adrenal cortisol overproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explain the discordance between the high level of hypercortisolism and the mild degree of ACTH overexpression in the tumor cells, we raised the possibility that this NSET may express another hormone triggering the pituitary-adrenal axis. We therefore measured the expression of CRH mRNA in tumor extracts and found high levels in the liver NSET compared with fetal placental control tissue (17), while normal human liver did not express CRH. This finding suggested that ectopic CRH originating from the NSET may have triggered the pituitary production of ACTH, thus stimulating adrenal cortisol overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…RT was performed at 37 8C for 60 min in presence of 1 mg of total RNA, using 50 pmol oligodT [12][13][14][15][16][17][18] , 0.2 mM of each deoxynucleotide triphosphate, 10 mM dithiothreitol, 5 U of RNasin and 200 U Moloney murine leukemia virus-RT (Invitrogen) in a final volume of 40 ml. The reaction was terminated by the inactivating enzyme at 95 8C for 5 min.…”
Section: Quantitative Pcr For Pomc 11b-hsd1 and Crh Mrnamentioning
confidence: 99%
“…[2][3][4][5][6] In addition, the gene encoding the CRH receptor type 1 (CRHR1) is expressed in human endometrial and myometrial cells, indicating a local effect of uterine CRH. 7,8 Indeed, locally produced CRH promotes implantation and maintenance of early pregnancy.…”
mentioning
confidence: 99%
“…All of the HPA and placental stress hormones increase as pregnancy advances, but the exponential increase in placental CRH in maternal plasma is especially dramatic, reaching levels observed only in the hypothalamic portal system during physiological stress (Lowry, 1993). The levels of hCRHmRNA increase more than 20-fold in the five weeks preceding delivery (Frim et al, 1988) resulting in a significant elevation in maternal CRH plasma concentrations during the second half of pregnancy. Levels rise exponentially as pregnancy advances, peaking during labor, and falling to very low or undetectable levels within 24 hours after delivery (Campbell et al, 1987;Chan et al, 1993;Goland et al, 1992;Sasaki et al, 1987;Wolfe et al, 1988).…”
Section: Endocrine Stress System During Pregnancymentioning
confidence: 99%